Paligorsquita como adsorvente para íons de metais de transição: Estudos cinéticos e do equilíbrio - Oliveira, Andréa Maria Brandão Mendes de (2011)
Clay minerals are silicates with importance of environmental, technological and academic view, existing in a large variety as synthetic or natural materials. In this group, the palygorskite is a clay mineral of fibrous habit with 2:1 structure and wide industrial application. This material shows a partial isomorphic substitution of magnesium with aluminum and/or iron and such substitutions result in an excess of negative charges. These charges are associated with specific surfaces resulting in the palygorskite an adsorbent for polar molecules or positive ions. In this work, the palygorskite of Piauí was applied as adsorbent in aqueous solution for removal of copper, cobalt and nickel from simple and binary solutions. The palygorskite was characterized by chemical analysis, XRD, infrared spectroscopy and thermogravimetry. The adsorption experiments for ions in aqueous solution were carried out by batch method in which the effect of reaction time (2-72 h), temperature (303, 313 and 323 K), initial concentration of metal ion (10-3 to 10-2 mol dm-3) at various temperature, pH (2.0, 4.0, 6.0 and 8.0) and ionic strength (solutions of NaNO3 at concentrations of 0.01; 0.005; 0.008 and 0,01 mol dm-3) were systematically varied. The binary mixtures of cations were investigated by varying the reaction time and the initial concentrations of ions in solution. The retention time was 48 h maximum for all cations. The data of time isotherm were fitted to kinetic models of pseudo first order, pseudo second order and intraparticle diffusion, where the data were best described by the second order kinetic model. The isotherms of concentration were fitted to the Langmuir and Freundlich models. The maximum capacities of adsorption for copper (II), nickel (II) and cobalt (II) were 1.28; 1.21 and 1.1 mmol g-1; 1.60; 1.46 and 1,40 mmol g-1 and 0.78; 0,68 and 0,61 mmol g-1 at 303, 313 and 323 K, respectively. The palygorskites saturated with cations were characterized by XRD, infrared spectroscopy and thermogravimetry showing insignificant changes in their structure comparing with the precursor solid.